EFFECT OF GENDER AND THE TYPES OF WRITTEN CORRECTIVE FEEDBACK ON THE L2 LEARNERS’ WRITING PERFORMANCE - Sabarun Sabarun (Universitas Muhammadiyah Semarang, 2019)
The study is aimed at measuring the influence of the types of WCF on EFL students’ writing performance with involving gender factors. The research design was a pretest-posttest quasi experimental design. A pre-post writing test for both experiment and control groups was the main instrument. The participants of the study were 72 L2 learners at IAIN Palangka Raya of 2018/ 2019 academic years. During the learning process, the experimental group 1 was given treatment using Direct Corrective Feedback (DCF); the experimental group 2 was given treatment using Indirect Corrective Feedback (ICF); and the control group was not given treatment or received No Feedback (NF). The data were analyzed using a two-way ANOVA analysis. The analysis revealed that there was a statistically different effect for the types of WCF on the learners’ writing performance (F= 34.354, p= 0.000). Meanwhile, there were no differences between gender to the learners’ writing performance (F= 0.739; p=0.393 eta squared= 0.011). The interaction effect of gender and types of feedback also did not show significantly different among other groups F (2,66) =.1.120; p= 0.332; eta squared= 0.033).